2013
DOI: 10.1557/opl.2013.797
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide releasing poly-(ethylene glycol)-fibrinogen adhesive hydrogels for tissue regeneration

Abstract: Nitric oxide (NO) release can promote healthy tissue regeneration. A PEG-fibrinogen adhesive hydrogel that would allow for inducible NO release was created with mechanical properties that could be tailored to specific applications and tissue types. PEG (4-arm)-fibrinogen hydrogels of varying ratios were derivatized with S-nitroso-N-acetyl-D, L-penicillamine (SNAP)-thiolactone to create an active NO donor material. Controlled release from gels was established using light as the activating source, although tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Genipin-cross-linked fibrin exhibited promise in functioning as an adhesive for repairing intervertebral disc annulus while demonstrating elastic modulus in the range of native annular tissue and remained adhered to the native tissue at strains exceeding physiological levels. Most recently, fibrin gel was functionalized with nitric oxide donors for preparing biomaterials capable of controlling release of nitric oxide for promoting tissue regeneration and wound healing [ 61 , 62 ].…”
Section: Future Outlookmentioning
confidence: 99%
“…Genipin-cross-linked fibrin exhibited promise in functioning as an adhesive for repairing intervertebral disc annulus while demonstrating elastic modulus in the range of native annular tissue and remained adhered to the native tissue at strains exceeding physiological levels. Most recently, fibrin gel was functionalized with nitric oxide donors for preparing biomaterials capable of controlling release of nitric oxide for promoting tissue regeneration and wound healing [ 61 , 62 ].…”
Section: Future Outlookmentioning
confidence: 99%
“…Previous studies from our group showed that primary amines on fibrin based hydrogels could be covalently modified with SNAP to create inducible NO-releasing scaffolds 1 and that PEG-NHS-fibrinogen composites could also be modified postgelation to create composite inducible NO-releasing scaffolds. 2 The direct-derivatization of fibrinogen to form SNAP-fibrinogen results in a dramatic loss of solubility in aqueous solutions precluding their use in generating reproducible gelation kinetics and hydrogel properties. Incorporating SNAP-fibrin microparticles into the PEG-Fgn matrix reduces the time required to prepare a NO-releasing hydrogel, and has also proven to be more reproducible than approaches using direct derivatization of fibrinogen.…”
Section: Acs Biomaterials Science and Engineeringmentioning
confidence: 99%
“…Their capacity to serve as barriers to adhesion formations, act as a stable provisional matrix for cell attachment and load transfer, and their broad potential for incorporating active elements (i.e., growth factors, protease inhibitors, platelets, and mesenchymal stem cells (MSCs)) to aid in wound healing has led to widespread interest for their use in soft tissue injury repair, including in ligaments and tendons. To that end and building on previous studies, , this work addresses the challenge to create a tissue adhesive composite hydrogel that can serve as a preliminary matrix for soft tissue wound repair as well as a delivery vehicle for active molecules that support the wound healing process. Specifically, we have created a novel composite poly­(ethylene) glycol- N -hydroxylsuccinimide (PEG-NHS)-fibrinogen adhesive hydrogel containing fibrin microparticles blended with the NO donor, S-nitroso-N-acetyl penicillamine (SNAP), to allow for the controlled release of nitric oxide as a wound healing support.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels have been utilized in various biomedical applications, functioning as tissue adhesives [23,24,112], tissue engineering scaffolds [113][114][115], drug delivery carriers [116,117], post-surgical adhesion barriers [118,119], and actuators [120,121]. However, conventional hydrogels are mechanically weak and have a very narrow elastic range.…”
Section: Nanocomposite Hydrogelmentioning
confidence: 99%